2022
DOI: 10.36407/jmsab.v4i2.401
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Transformasi Organisasi Terhadap Kinerja Dengan Motivasi Dan Kompensasi Sebagai Variabel Mediasi Pada Personil Project Management Office PT Perusahaan Gas Negara Tbk

Abstract: The main objective of this study is to examine and analyze the effect of organizational transformation on performance with motivation and compensation as mediating variables in the project management office (“PMO”) personnel of PT Perusahaan Gas Negara Tbk. (“PGN”) by using a quantitative descriptive approach. The data in this study were obtained from PMO organic employees who work at PGN. The total population of PMO organic employees at the time the research was conducted was 118 (one hundred and eighteen) pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Transformational management positively and significantly affect the employees' performance (Harahap, 2020). Organizational transformation significantly affect the employees' performance (Wijayatma et al, 2022). The basic assumption in the formulation of the hypothesis that organizational transformation is able to increase enthusiasm and new hopes for all employees.…”
Section: The Effect Of Organizational Transformation On Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformational management positively and significantly affect the employees' performance (Harahap, 2020). Organizational transformation significantly affect the employees' performance (Wijayatma et al, 2022). The basic assumption in the formulation of the hypothesis that organizational transformation is able to increase enthusiasm and new hopes for all employees.…”
Section: The Effect Of Organizational Transformation On Job Satisfactionmentioning
confidence: 99%
“…A study conducted by Wijayatma et al (2022) demonstrated that organizational transformation implementation positively and significantly affect the employees' performance. The main objective of organizational transformation is to seek new methods or improve the utilization of the resources and capabilities of the organization with the aim of increasing the organization's ability to create added value and obtain performance targets desired by stakeholders.…”
Section: The Effect Of Organizational Transformation On Employee Perf...mentioning
confidence: 99%